Sobolev and Lipschitz regularity for local minimizers of widely degenerate anisotropic functionals. (April 2017) - Brasco, Lorenzo; Leone, Chiara; Pisante, Giovanni; Verde, Anna
Abstract: We prove higher differentiability of bounded local minimizers to some widely degenerate functionals, verifying superquadratic anisotropic growth conditions. In the two dimensional case, we prove that local minimizers to a model functional are locally Lipschitz continuous functions, without any restriction on the anisotropy.